The impact of referral wait times on high‐risk medication usage in patients with chronic pain: a tertiary pain clinic retrospective chart audit. - Tynan, Kristin E.; Borg, Samantha J.; Aitcheson, Nicholas; Cheung, Christy; Ownsworth, Tamara (Journal of Pharmacy Practice & Research, 2025)
Background: Increasing demand for specialist pain clinics for patients with chronic non‐cancer pain has led to longer wait times. The shift towards multimodal analgesia has raised significant safety concerns, particularly in vulnerable populations, yet remains unexplored. Aim: This study aimed to investigate changes in medication use for opioids, gabapentinoids, and benzodiazepines among patients waiting for an initial appointment at a tertiary pain clinic, and to determine the effect of waitlist duration on opioid doses. Method: A retrospective audit of patients referred to a pain clinic between January 2022–December 2023 was conducted at a public tertiary hospital, located in Queensland, Australia. Data from general practitioner referrals and first appointments were analysed. Negative binomial regression examined the relationship between waitlist duration and opioid dosages. This project was exempt due to the local policy requirements that constitute research by the Metro South Health Human Research Ethics Committee (Reference no: EX/2023/QMS/98214). The justification for this exemption was as follows: the project only utilised anonymised data collected as part of routine clinical practice, presented minimal patient risk, and conforms with the National Health and Medical Research Council Ethical considerations in quality assistance and evaluation activities. Results: The study included 500 patients with complete data, of whom 82% reported using prescribed opioids at referral, 42% reporting using gabapentinoids, and 25% reported using benzodiazepines. Concomitant use was common, with 43% of patients on opioids plus at least one other medication class at referral. The median waitlist duration was 320 days. After adjusting for covariates, there was no effect of waitlist duration on opioid doses at first appointment. Referral opioid dose was the strongest predictor of first appointment opioid dose (odds ratio 1.01, 95% confidence interval 1.009–1.012, p < 0.001). Conclusion: Despite no effect of waitlist duration on opioid doses, high rates of concurrent medication use highlight the need for improved triage systems and management strategies to reduce risks and optimise care.